1986
DOI: 10.1007/bf00586681
|View full text |Cite
|
Sign up to set email alerts
|

Effects of brain and trunk temperatures on exercise performance in goats

Abstract: In 40 experiments on seven goats head and trunk temperatures were altered independently of each other and the effects on exercise performance on a treadmill (speed: 3 km/h, slope: 16%-20%) were observed. Brain temperature between 38.5 degrees C and 42.0 degrees C and trunk temperature between 39 degrees C and 43.5 degrees C did not reduce exercise performance or running time. Blood lactate concentration increased with rising brain and trunk temperatures, but did not exceed 13.1 mmol/l-1. Blood pressure and hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(51 citation statements)
references
References 25 publications
3
48
0
Order By: Relevance
“…Evidence in humans and animals also supports the notion that fatigue in hot environments appears to coincide with a critically high internal body temperature (6,11,12,14,17,24). There are reports indicating that some untrained subjects fatigued during exercise in uncompensable hot environments with body temperatures of ϳ38°C (23,26,38).…”
Section: High Temperature and Fatiguementioning
confidence: 66%
“…Evidence in humans and animals also supports the notion that fatigue in hot environments appears to coincide with a critically high internal body temperature (6,11,12,14,17,24). There are reports indicating that some untrained subjects fatigued during exercise in uncompensable hot environments with body temperatures of ϳ38°C (23,26,38).…”
Section: High Temperature and Fatiguementioning
confidence: 66%
“…Selective brain cooling has been viewed as a mechanism which can protect the brain from overheating (Carithers & Seagrave, 1976) and extend the range of body core temperature over which an animal can function in hot environments and during exercise (Taylor & Lyman, 1972). However, the observation that goats can withstand brain temperatures of 42-5°C without apparent deleterious effect (Caputa, Feistkorn & Jessen, 1986) suggested that the vulnerability of the brain to thermal damage might not be as important as once believed (Burger & Fuhrman, 1964). Recently, Kuhnen & Jessen (1991) showed that SBC occurs in the normothermic range of body temperatures in goats and proposed that SBC is 'a thermoregulatory effector mechanism like shivering or panting', with thermostasis of the head rather than of the general body core as the net result.…”
Section: Introductionmentioning
confidence: 99%
“…Both studies showed a linear relationship between α β T c during exercise hyperthermia. Further evidence to support the idea of high brain temperature as a limiting factor during exercise comes from research demonstrating attenuated running performance in goats after elevating hypothalamic temperature (Caputa et al, 1986). Based on these findings, investigators hypothesize that inhibitory signals arise from temperature-sensitive areas in the hypothalamus and attenuate motor activity when body temperature rises (Nybo & Nielsen, 2001a;Nybo, 2012).…”
Section: Central-related Factorsmentioning
confidence: 99%